Analisis Investasi, Ekspor, dan Kurs terhadap Produk Domestik Regional Bruto di Provinsi Maluku, 1986-2009: Pendekatan Error Correction - Marthen Anthon Pentury (EKO-REGIONAL, 2011)
This study focuses on the analysis of gross domestic regional product and macro variables in the region of Maluku Province. The dependent variable was the Gross domestic regional product (Y), while the independent variables which are the target of observation is the investment variable (X1), the export variable (X2) and the exchange rate variable (X3). Data used in this study originated from the BPS, BI and the BKPMD of Maluku Province. The method used in this study is EG-ECM (Engle Granger – Error Correction Model). Results showed that in the short term variable investment and export has a positive direction and significant at 5 percent level while the exchange rate has a negative direction and significant at level 10 percent. In the long-term all variable has a significant at 5 percent level, investment and export has a positive direction and exchange rate has a negative. ECT is a significant value indicates that the model used in this study is valid. Keywords:GDRP, investment, export and exchange rate